(untitled) (Journal of the Bangladesh Agricultural University, 2016)
An attempt was taken to transform Aman-fallow-Boro cropping pattern into Aman-rapeseed and mustard-Boro for three years beginning from Rabi 2011-12. Two components viz. Bangladesh Agricultural University, Mymensingh (BAU) and Bittohin Chashi Somaj Kallayan Sangstha (BCSKS) executed the programme under the leadership of BAU. Three upazillas viz. Mymensingh Sadar, Muktagacha & Haluaghat of Mymensingh district were under BAU component. Whereas, the upazillas Bagha of Rajshahi, Ishwardi of Pabna and Lalpur of Natore districts were under BCSKS component. A total of 1200 farmers (300+400+500 for 1st, 2nd & 3rd years) were taken into consideration to grow rapeseed and mustard in between Aman & Boro. Each of the farmers were provided with 1kg rapeseed and mustard seeds, necessary fertilizers, insecticide, fungicide & irrigation costs. Five rapeseed and mustard varieties namely BARI sarisha 14 & 15, BINA sarisha 4 & 7 and Unnata Tori 7 were used. Before rapeseed and mustard cultivation, all the farmers grew Aman rice &Boro rice after harvesting it. Among the five rapeseed and mustard varieties BARI sarisha 14 & 15, BINA sarisha 4 and Unnata Tori 7 were found to be suitable for the cropping pattern Aman-rapeseed and mustard-Boro. These varieties matured between 76.9 to 84.1 days. Per hectare seed yield of the varieties ranged from 1266.5 kg (Unnata Tori 7) to 1822.0 kg (BARI sarisha 14) with an average of 1544.6 kg. On an average per hectare cost of production, gross income & gross return from rapeseed and mustard were tk. 27770, 78180 and 50471, respectively. On an average, over three years gross income and gross return obtained from Aman and Boro rice were tk. 52,273 &22237 and tk. 71,138 & 30,935 per hectare, respectively. Thus, an additional income of tk. 50471 obtained by the farmers for growing rapeseed and mustard in between Aman & Boro over that of Aman & Boro only, and cropping intensity of the farmers raised into 300%. J. Bangladesh Agril. Univ. 13(1): 1-6, June 2015